Mapeamento do potencial de produção de biogás no Estado do Paraná à partir de dejetos de suínos e bovinos leiteiros - Barizon, Fernanda (2020)
Livestock has a great economic importance in Parana state, Brazil. In this scenario, the Southwest region stands out as the biggest dairy producer and second biggest swine producer of the state. As a consequence of this production there is a waste generation, which brings negative impacts to the environment. Using the waste in the biogas production chain is a way of reusing and minimizing these impacts. Therefore, the goal of this study was to estimate the biogas production potential of the livestock waste in Parana, with emphasis in the Southwest region, with different methodologies adapted to the reality of this region. For this purpose, it was gathered information about the quantity of swine and dairy cattle in all municipalities of the state. Based on that, IPCC (2006) and CIBiogás (2009) methodologies were selected and compared in order to perform the estimate biogas production. The methodologies were used in their original format and with data adapted from similar studies of region conditions to the Southwest region. Besides that, it was estimated the biogas contribution in the electrical, thermal and vehicular energy supply of the region and of the state. The results show that both methodologies when used with the adapted data present higher results than the ones attained with the methodology in its original format. Comparing both, CIBiogás (2009) methodology provides results adapted to the reality of each region in study. Regarding both animal categories studied, it is possible to notice a prevalence of the biogas production potential when it is estimated from dairy cattle waste (63% higher), mainly due to the great difference among the herds. The West and Southwest mesoregions stand out both for their dairy cattle (2238,9 m³biogas.d-1 and 2733,5 m³biogas.d-1, respectively) and swine potential (4869,2 m³biogas.day-1 and 525,9 m³biogas.d-1, respectively). It was concluded that the state has a great potential for the biogas production (12779,5 m³biogas.d-1 from dairy cattle, and 7847,7 m³biogas.d-1 from swine), however, the viability of implementing projects must be analyzed according to its potentials and constraints. Finally, we conclude that the reinsertion of livestock waste through the biogas production allows the transformation of an environmental passive to an environmental asset.